Peningkatan Hasil Belajar IPS Menggunakan Metode Two Stay Two Stray Melalui Pemberian Reward Bintang pada Siswa - Lies Maryati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The problem in this study is how to improve social studies learning outcomes using the two stay two stray method by giving star rewards to class VII students of SMPN 3 Kandis. The purpose of this study was to describe how to improve social studies learning outcomes using the two stay two stray method by giving star rewards to seventh grade students of SMPN 3 Kandis. The method used in this research is a classroom action research method with 2 cycles. From the results of the study, it is known that in the first cycle the number of students' complete learning outcomes is 73% and in the second cycle the number of students' complete learning outcomes is 80%. This means that there is an increase of 10%. Thus, it can be concluded that the two-stray two-stray method through the provision of star rewards can significantly improve social studies learning outcomes for seventh grade students of SMPN 3 Kandis.